Liberals Possess More National Consensus on Political Attitudes in the United States: An Examination Across 40 Years. Issue 8 (November 2018) - Ondish, Peter; Stern, Chadly
Do liberals or conservatives have more agreement in their political attitudes? Recent research indicates that conservatives may have more like-minded social groups than do liberals, but whether conservatives have more consensus on a broad, national level remains an open question. Using two nationally representative data sets (the General Social Survey and the American National Election Studies), we examined the attitudes of over 80, 000 people on more than 400 political issues (e.g., attitudes toward welfare, gun control, same-sex marriage) across approximately 40 years. In both data sets, we found that liberals possessed a larger degree of agreement in their political attitudes than did conservatives. Additionally, both liberals and conservatives possessed more consensus than did political moderates. These results indicate that social–cognitive motivations for building similarity and consensus within one's self-created social groups may also yield less consensus on a broad, national level. We discuss implications for effective political mobilization and social change.